Psikologi Agama: Analisis Bibliometrik pada Database Dimensions - Annissa Rachma Gustiyanti; Busro Busro (UIN Sunan Gunung Djati Bandung, 2023)
In the way of thinking, reacting to a problem, how to socialize, or behaving in society, everything is inseparable from the psychological role and one's beliefs. This study aims to map Bibliometric data in the Dimensions database. This study uses a quantitative method which identifies the development of articles with the theme of the psychology of religion by analyzing the Dimension database. The results of the study show that the psychology of religion is in great demand, especially in the field of educational research. Developments regarding religious psychology articles have also increased quite significantly from year to year. Advances in Social Sciences, Education and Humanities Research are seen in the most published articles on the psychology of religion. The benefit of this research is to find out mapping data on religious psychology research.